2016
DOI: 10.3389/fnana.2016.00048
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Organization of Deep Brain Opsin Photoreceptors in Adult Teleosts

Abstract: Biological impacts of light beyond vision, i.e., non-visual functions of light, signify the need to better understand light detection (or photoreception) systems in vertebrates. Photopigments, which comprise light-absorbing chromophores bound to a variety of G-protein coupled receptor opsins, are responsible for visual and non-visual photoreception. Non-visual opsin photopigments in the retina of mammals and extra-retinal tissues of non-mammals play an important role in non-image-forming functions of light, e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…However, in the same study, the authors demonstrated that not all brain nuclei are photosensitive, raising the possibility that even in zebrafish, the different oscillators are not as independently entrained by light as initially thought (Moore & Whitmore 2014). A widespread photosensitive ability may not be a rule in other teleosts as, to date, the existence of photoreceptors has been demonstrated in the pineal gland, retina and deep brain photoreceptors (Menaker et al 1997, Davies et al 2015, Hang et al 2016; blue in Fig. 1), but not in peripheral tissues, although their existence cannot be ruled out (Davies et al 2015).…”
Section: :3mentioning
confidence: 94%
“…However, in the same study, the authors demonstrated that not all brain nuclei are photosensitive, raising the possibility that even in zebrafish, the different oscillators are not as independently entrained by light as initially thought (Moore & Whitmore 2014). A widespread photosensitive ability may not be a rule in other teleosts as, to date, the existence of photoreceptors has been demonstrated in the pineal gland, retina and deep brain photoreceptors (Menaker et al 1997, Davies et al 2015, Hang et al 2016; blue in Fig. 1), but not in peripheral tissues, although their existence cannot be ruled out (Davies et al 2015).…”
Section: :3mentioning
confidence: 94%
“…Other circadian cellular photopigments are the so-called deep brain photoreceptors (different nonvisual opsins) of non-mammalian vertebrates (Davies et al 2015;Hang et al 2016). In mammals, functional deep brain opsins have so far not been identified, but melanopsin in a subset of the retinal ganglion cells fulfils the role as circadian cellular photopigment (Provencio et al 1998;Berson et al 2002;Hattar et al 2002;reviewed in Lazzerini Ospri et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The possible contribution of ONT light can only be minor in this context, however, since the light reaching the retina through the conventional pathway stimulates the photosensitive cells as well. Teleosts also possess several photosensitive brain areas, not only in the pineal but also throughout the deep brain, that are involved in many regulatory processes [ 33 ]. Both the translucency of the skull and the light guidance by the optic nerves could originally be adaptations that allow light to reach those brain areas.…”
Section: Resultsmentioning
confidence: 99%